Czy klimatyzacja jest prawem człowieka? O odpowiedzialności państwa za przeciwdziałanie skutkom globalnego ocieplenia na gruncie Konstytucji Rzeczypospolitej Polskiej - Kazimierski, Damian; Wardecki, Władysław (Studia Prawa Publicznego, 2024)
In the age of noticeable climate change, enduring high temperatures is becoming a serious problem and inconvenience, which can cause health problems and even lead to death. One way to counteract the negative effects of heatwaves is to use an indoor air-conditioning system – both in residential building and in workplaces. The purpose of the article is to find an answer to the question posed in the title of the publication of whether access to an air-conditioned room can be considered, on the basis of the Constitution of the Republic of Poland, to be a human right. The considerations are divided into two segments: the right to air-conditioning in the workplace as part of the employer’s provision of safe and hygienic conditions, and the state’s responsibility for counteracting the negative effects of climate change. Indeed, it turns out that the Polish constitution makes it possible to conclude that the state has a certain obligation to provide places of rest from the heat in a situation where it threatens health and life. The article presents selected solutions for counteracting the effects of hot weather in European cities where high temperatures are more frequently recorded than in Poland. In addition, it presents the scope of the obligation to ensure adequate comfort at work in conditions with a high air temperature that also falls on employers. The aim is to draw attention to the important issue of how public authorities can counteract the negative effects of global warming. Indicating solutions used in other countries, it seeks an appropriate way for public authorities to act in Poland.